The economic value of wetland conservation and creation: A meta-analysis - Andrea Ghermandi; J. C. J. M. van den Bergh; L. M. Brander; P. A. L. D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2008)
The rationale for conservation and creation of wetlands stems from the recognition of both their ecological and economic values. This paper examines the welfare impacts of goods and services provided by wetlands. We collected 385 estimates of the economic value of 181 natural and man-made wetlands from 167 studies worldwide. The resulting database is less biased towards North America than previous reviews of the literature. The relative importance of characteristics of the valuation study, of the wetland site, and of the socio-economic and geographical context is estimated by means of a meta-regression analysis of wetland values. Provision of amenities, flood control and storm buffering, and water quality improvement are the most highly valued wetland services. The relevance of the socio-economic and geographical context clearly emerges from the analysis and, in particular, the proximity to other wetland sites is negatively correlated with valuations. An analysis of the effect of environmental stress on wetland value shows that the latter increases with stress from human development activities and uses. In addition to the basic meta-regression model, the influence of authorship effects and of the geographic regions is examined by means of a multi-level approach. A second extended meta-regression model including cross-effects shows that the valuations of specific services vary according to the type of wetland producing them.
Keywords: C81; Q24; 330; Constructed Ecosystems; Economic Valuation; Man-Made Wetlands; Meta-Regression; Wetland Values